THE IMPACT OF INFORMATION ABOUT CLIENT IN MODERATED THE EFFECT OF THE INVOLVEMENT OF PUBLIC ACCOUNTING FIRM HEAD AND THE EFFECT OF PROBLEM REPRESENTATIONS ON AUDIT PLANNING - Amilin Amilin; Dennis Steven Erthanegara (Jurnal Akuntansi, 2013)
This research examined the effect of executive involvement and problem representation toward audit planning using client’s information as moderating variable. The populations are managing partners, partners, and managers on the public accountant firm that located in DKI Jakarta. Purposive sampling used to take the samples. The sample was taken about 34 respondents which collected by using questionnaires. The analysis methods were consist of test quality data, descriptive statistic, classical assumption test, and hypotheses analysis used test of absolute difference value. The result of hypotheses analysis show that client information have not significantly impact on the influence of executive involvement and problem representation on audit planning.